Making the kettle boil Rights talk and political mobilisation around electricity and water services in Soweto - McInnes, Peter Charles (My University, 2006)
This dissertation looks at the attitudes, actions and opinions towards law, rights and political mobilisation, and in particular South Africa’s Bill of Rights, of a small band of activists associated with the Soweto Electricity Crisis Committee (SECC). It provides a snapshot of attitudes towards the Bill of Rights prevalent at the birth of a small organisation, which since 2000 has been active and at times successful in guaranteeing affordable electricity in South Africa’s largest township - Soweto. The SECC emerged as a real force in Johannesburg’s political life in the first half of 2001 as a result of the disconnection of up to 20,000 households per month by the state owned electricity utility, ESKOM. In response to these cut-offs Sowetans required urgent and appropriate forms of political action that would both provide immediate relief in terms of reconnecting disconnected households to the grid, wiping off unpayable electricity account arrears and, over the longer term, mitigating or transforming the policies that led to the cut-offs. This study explores to what extent the Bill of Rights enhanced grass roots political mobilisation. The study describes the potential mechanism through which rights discourse promotes community mobilization and provide some preliminary comments on the appropriateness of legal mobilization for political ends. This focus on electricity enabled understanding of how a community based organisation strategised social mobilisation when a particular demand, in this case an essential service - electricity - is not explicitly included in the South African Bill of Rights. Specifically it allowed the study of strategies adopted to prosecute similar demands surrounding access to water, which was explicitly included in the Constitution. In this case the SECC strategy was to deliberately obscure the boundaries between the two services. Rights talk was adopted by the SECC to serve political ends. The need of Sowetans for reliable, consistent and affordable supplies of electricity was transformed and demanded as of right by the SECC. Such a characterisation had obvious advantages to the SECC activists trying to build a movement that could challenge Eskom’s and the municipal government’s credit control policies. Rights talk provided a catalyst to engage interest in the campaign. On attracting an audience by ‘rights talk’ the allegation that service disconnection denied ‘fundamental human rights’ tapped into already existing feelings of hurt and humiliation. Rights talk legitimated peoples private feelings of pain and humiliation. The evolving sense of outrage as a result of this denial was then directed (hopefully) towards involvement in protests and meetings. The themes present in the writings of critical legal theorists on rights are explored. This study found that the key tenets of critical legal theory’s critique of rights such as the malleability and indeterminacy of legal discourse to suit your own ends; the tilt within the legal system to already powerful interests within South African society; and the risks of constitutional litigation to the democratic character of the struggle were all present in the minds of activists. Yet ultimately legal strategies were of ongoing interest to SECC activists because of the undeniable potential leverage they provided to promote social mobilisation and allow for real changes in harmful government policies through the assistance of the courts. These potential uses outweighed the identified attendant risks of a constitutional litigation strategy. This study concludes that rights can form an important component of the progressive activists arsenal of weapons against liberal capitalism. This is both understandable in a short-term strategic sense (as implied above in the SECC’s use of rights) as well as a more complex longer-term project of building a better society.
Faculty of Humanities School of Humanities and Social Sciences 0200487m peter.mcinnes@health.gov.za
Keywords: Bill of Rights; Essential Services; Elcetricity; Water Utilities; Critical Legal Studies